Brewing : new technologies - Bamforth, Charles W. , 1952- (Cambridge : Woodhead Publishing, 2006)
This book comprehensively describes the the brewing of beer, from raw materials supply, through processing, to the final product and its analysis
Includes index
Keywords: Brewing; Brewing -- Technological innovations